Teknologi Bluetooth dengan Mekanisme Multihop - Endar Nirmala (Program Studi Teknik Informatika Universitas Pamulang, 2019)
Bluetooth is a wireless communication technology that is used to exchange information, at a lower cost, use low power, the ability to work or interact between applications through approved protocols is very good, and easy operation. The Bluetooth operating range works on the 2.4 GHz unlicensed ISM (Industrial, Scientific and Medical) frequency band using a frequency hopping tranceiver that is able to provide real-time data and voice communication services between Bluetooth hosts. When Bluetooth devices communicate with each other, they will form a dynamic network called piconet, a network consisting of master and slave, in one piconet of no more than 7 slaves. Bluetooth also supports connections between piconets called scattemets. The mechanism for connecting between one piconet and another is called a hop mechanism.